The Complex Trauma Questionnaire (ComplexTQ): development and preliminary psychometric properties of an instrument for measuring early relational trauma - Maggiora Vergano, Carola; Lauriola, Marco; Speranza, Anna Maria (Frontiers in Psychology, 2015)
Research on the etiology of adult psychopathology and its relationship with childhood trauma has focused primarily on specific forms of maltreatment. This study developed an instrument for the assessment of childhood and adolescence trauma that would aid in identifying the role of co-occurring childhood stressors and chronic adverse conditions. The Complex Trauma Questionnaire (ComplexTQ), in both clinician and self-report versions, is a measure for the assessment of multi-type maltreatment: physical, psychological, and sexual abuse; physical and emotional neglect as well as other traumatic experiences, such rejection, role reversal, witnessing domestic violence, separations, and losses. The four-point Likert scale allows to specifically indicate with which caregiver the traumatic experience has occurred. A total of 229 participants, a sample of 79 nonclinical and that of 150 high-risk and clinical participants, were assessed with the ComplexTQ clinician version applied to Adult Attachment Interview (AAI) transcripts. Initial analyses indicate acceptable inter-rater reliability. A good fit to a 6-factor model regarding the experience with the mother and to a 5-factor model with the experience with the father was obtained; the internal consistency of factors derived was good. Convergent validity was provided with the AAI scales. ComplexTQ factors discriminated normative from high-risk and clinical samples. The findings suggest a promising, reliable, and valid measurement of early relational trauma that is reported; furthermore, it is easy to complete and is useful for both research and clinical practice.